SOME AMBIGUITIES OF THE SCIENCE OF HUMAN KINETICS (CMH) (Fiep Bulletin - online, 2012)
The document presents, in a very brief way, five ambiguities that we considered crucial to approachfacing the evolution of the science of human kinetics.
Keywords: mobility; science; capacity; ambiguity